Bilateral index, power, force, and velocity during bench press with different loads in male handball players - González-Ramírez, Andrés; Torres, Carol; Magallanes, Carlos; Fábrica, Carlos Gabriel (Frontiers in Physiology, 2023)
Bilateral index for upper limbs was determined for maximal force, speed and power in 18 male handball players. Variables were individually assessed with a functional electromechanical dynamometer during unilateral and bilateral bench press push-off for 40%, 60%, and 75% of the maximal isometric force. Limb dominance (symmetry indices) and load effects in the bilateral index were analysed. Bilateral index showed a bilateral deficit for power (range = −8.50 to −41.48) and velocity (range = −11.15 to −38.41), that increases with the load (p < 0.05). For maximum force, a bilateral facilitation (range = 2.26–5.57), which did not vary significantly as a function of load, was observed. Symmetry indices showed no association with the bilateral index (40% load: r = 0.45, 60% load: r = 0.05, 75% load: r = 0.39). These results contribute to understanding the phenomenon; however, individual-to-individual observation reflects that caution should be kept when assessing an individual athlete. In conclusion, bilateral deficit or facilitation for bench press depends on the variable considered, whereas its magnitude depends on the load. Moreover, limb dominance does not affect it. This finding must be regarded as a general trend, but a different situation may occur during the assessment of a particular athlete.